It is necessary to find a meeting point between pupil’s directive and non-directive orientation. (Journal of Parents and Teachers, 2014)
In the event of conflicts with children or students, two types of measures can be taken. On the one hand, there are the directives, among which we can differentiate 7 different types, among which we find: judge, cut, minimize. . . On the other hand, there are the non-directive measures, of which there are also 7 types and we can find: silence/wait, monosyllables, etc. ¿But which type is better at solving a conflict? In the following article we present a research with parents and their journey through both methods, in order to reach a meeting point between them.
Keywords: directive orientation; non-directive orientation; measures; laberynth; conflicts